Biodegradable Thermogelling Polymers. Issue 3 (11th December 2018) - Loh, Xian Jun; Chee, Pei Lin; Owh, Cally
Abstract: Thermogelling materials are envisioned as smart biomaterials with significant potential in the biomedical field. Their importance lies at the intersection between two highly medically relevant classes of materials: hydrogels and smart materials. They possess high water content and tunable properties of hydrogels and the ability to respond to external temperature variations with a simple, physical, and reversible sol‐to‐gel phase transition. Thermogels are proposed for many uses including drug delivery, gene delivery, and scaffolding for tissue engineering. Recent developments of biodegradable thermogelling polymers are reviewed, focusing on the properties of different thermogel systems and how those properties correlate with biomaterials behavior with the goal of providing safe and effective treatment for the treatment of diseases such as diabetes, glaucoma, and cancer. Abstract : Society ages and problems such as organ damage or failure among senior citizens increases, raising the demand for organ repair technologies. Synthetic materials are developed and applied in the human body to meet biomedical needs. Thermogels, in particular, have found extensive applications in wound healing, drug delivery and controlled release, and scaffold materials in the human body.